Desempenho de bovinos de corte alimentados com milho ou sorgo na terminação. - Augusto, Wescley Faccini (Universidade Federal do Tocantins, 2023)
Two experiments were conducted to evaluate the performance, carcass and meat characteristics of beef cattle finished in feedlot. In Experiment I, 96 young European Zebu crossbreds bulls with 19 months of age and average initial weight of 373.0 kg were distributed in 16 collective pens (6 animals/pen) and fed during 74 days. The experimental design was the completely randomized with treatments distributed in factorial 2 x 2 arrangement, diets containing two levels of concentrate (CL) (medium, 530.0 g/kg DM and high, 820.0 g/kg DM) and two sources of energy in the concentrate (grounded corn or sorghum). In Experiment II, we used 11 young bulls and 11 heifers, F1 Angus x Nellore, with 18 months of age and average initial body weight of 354.0 kg. The experimental design was completely randomized with two sexual conditions, heifers and young bulls, with 11 replicates. The animals were confined for 93 days with a diet containing corn silage and 800 g/kg concentrate. In experiment I, the animals that consumed medium CL had higher total dry matter intake (10.95 versus 10.27 kg/day) and relative to body weight (24.58 versus 23.20 g/kg BW), regardless of corn or sorghum as energy source. The animals that received medium CL had higher (P<0.05) consumption of neutral detergent fiber (NDF) (3.50 kg/day and 7.95 g/kg BW) compared to animals fed high CL (1.89 kg/day to 4.30 g/kg BW). Likewise, the animals fed with medium CL diets had greater crude protein intake (P<0.05). Increasing concentrate level promoted increase in blood triglycerides and reduction in urea level. None of the variables related to the carcass and meat characteristics were altered (P>0.05) by treatments. In Experiment II, the average daily dry matter intake, average daily weight gain and feed conversion were not affected (P>0.05) by sexual condition. The hot carcass weight (284.62 vs 268.16 kg) and subcutaneous fat thickness (12.09 vs 13.05 mm) were similar between the sexual conditions. The hot carcass yield was higher in steers (58.14 vs 55.53 kg/100kg SW; P<0.05). The steers carcasses had higher proportion of forequarter (39.26 vs 37.53 kg/100 kg CC; P <0.05) and the heifers higher proportion of pistol cut (49.87 vs 48.85 kg/100kg CC; P<0.05). The meat shear force and the marbling score did not differ between the sexual conditions, with mean values of 5.43 kgf/cm2 and 10.14 points (medium), respectively. The use of alternative energetic food and manipulation of roughage:concentrate proportion in the diet of cattle in the finishing phase are important variables in the production system, mainly related to the cost and availability of grain in the market. Except for the proportion of primary cuts and hot carcass yield, F1 Angus x Nellore young heifers have carcass characteristics and meat similar to steers.